الأبعاد الجيوسياسية لظاهرة غسيل الأموال في النظام الدولي المعاصر (Comprehensive Journal of Science, 2025)
Money laundering is one of the most prominent challenges facing the international system in the twenty-first century, posing a dual threat to both economic and political security. Money laundering is no longer a financial phenomenon confined to economic crimes; it has become a geopolitical tool that influences the balance of power and relations between states, especially in light of financial globalization and market liberalization. This study aims to analyze the geopolitical dimensions of money laundering from an international relations perspective. It examines the links between illicit financial activity and states' foreign policies, and examines its implications for international security, the stability of political systems, and the role of international organizations in combating it. The study adopts an analytical approach that combines geopolitical and economic approaches to explain how the movement of illicit funds has become an influential factor in international decision-making and in reshaping the balance of influence and hegemony in the contemporary global system.